Evaluation on the application mode of blockchain technology in water transportation engineering project management - Liyu Lu (Water Supply, 2023)
Due to the continuous development and application of blockchain technology, more and more industries are exploring its application in project management. In the management of water transportation engineering projects, blockchain technology also has certain application potential. This article will start with the characteristics of blockchain technology, and the current situation and needs of water transportation project management, analyze the application mode of blockchain technology in water transportation project management, and explore its advantages, limitations, and practical applications. The experimental results of this article showed that when blockchain technology was applied to the management of water transportation engineering projects, its information sharing score was 93; its data storage and management score was 96.1; its smart contract score was 97.4; its fund management score was 97.1; its Internet of Things technology score was 96.5, which was far higher than the score of applying traditional technologies. It was shown that using blockchain technology for water transportation engineering project management can improve the efficiency and quality of project management, reduce costs, and extend to a wider range of water transportation lines and project fields in the future. HIGHLIGHTS With the continuous development of blockchain technology, its application in water transportation project management is also deepening.; This article starts from the characteristics of blockchain technology, the current situation and needs of water transportation project management, analyzes the application model of blockchain technology in water transportation project management, and discusses its advantages, limitations and practical applications.; The research results of this article show that using blockchain technology for water transportation project management can improve the efficiency and quality of project management and reduce costs.;